The Humanist Expressive Speech Acts of Journalists in the Covid-19 Outbreak - Supriyono, Areni Yulitawati; Zulaeha, Ida; Yuniawan, Tommi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research aims to analyze the humanist expressive speech acts of journalists in the covid-19 outbreak. The data collection technique was carried out by using the free non-participatory technique. The sources of data are the journalists’ utterances on YouTube in the covid-19 Outbreak. The humanist expressive speech act forms used by journalists, is 58% used the direct speech act forms with imperative, interrogative, and declarative modes; and 42% forms of indirect speech acts were declarative-imperative and declarative-interrogative modes. Results of this study shows that journalists use the forms of direct speech acts with declarative mode mostly. The form of indirect speech acts with the declarative-imperative mode are mostly used by the journalists. This research is important to be a journalist's guide so that the utterances spoken can be accepted by the society in the covid-19 outbreak